2013
DOI: 10.1590/s1516-05722013000200018
|View full text |Cite
|
Sign up to set email alerts
|

Atividade anti-helmíntica de plantas nativas do continente americano: uma revisão

Abstract: Anthelmintic activity of native American plants: a review. This paper is a review of native American plants showing anthelmintic activity in order to give support to research and development of new drugs in the field of natural products. In the literature, 22 plant families were cited, such as: Moraceae, Asteraceae and Cucurbitaceae, and around 35 species were studied, including Ficus sp, Cucurbita maxima and Ruta graveolens, used for their putative anthelmintic activity. From these species, 26 were active aga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
5

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 18 publications
0
5
0
5
Order By: Relevance
“…Outro aspecto importante no uso de plantas é que além de possuírem compostos bioativos com propriedades medicinais, apresentam baixo custo (Sousa et al 2013).…”
Section: Introductionunclassified
“…Outro aspecto importante no uso de plantas é que além de possuírem compostos bioativos com propriedades medicinais, apresentam baixo custo (Sousa et al 2013).…”
Section: Introductionunclassified
“…Of all the plants that have been studied, the anthelmintic activity was confirmed by in vitro or in vivo studies and, depending on the plant species or investigated parasite, this activity was or was not confirmed (Sousa et al, 2013;Camurça-Vasconcelos et al, 2005). It is therefore necessary when evaluating the anthelmintic activity of plant extracts to consider at least important factors, including: type of extract, plant part used, concentration / dose, route of administration, bioassay used, infected animal species and parasite species.…”
Section: Resultsmentioning
confidence: 99%
“…Author(s) agree that this article remain permanently open access under the terms of the Creative Commons Attribution License 4.0 International License and larvicidal activity against various parasites (Lone et al, 2012;Bi and Goyal, 2012;Sousa et al, 2013).…”
Section: Introductionmentioning
confidence: 89%
“…In this regard, various studies employing medicinal plants and their derivatives have shown ovicidal and larvicidal activities against several parasites (8)(9)(10)(11)(12)). An in vitro study, conducted by Macedo et al (8) with the essential oil of Eucalyptus globulus L. on hatching and development of Haemonchus contortus larvae, a gastrointestinal nematode of ruminants, showed ovicidal and/or larvicidal activity and potential for use in its control.…”
Section: Introductionmentioning
confidence: 99%
“…A study involving Carica papaya L. extract, suggested a potential role for this plant as an anthelmintic against infections caused by A. caninum in mice (10,11). Another, in vitro study showed larvicidal activity of leaf extracts from C. ambrosioides L., against T. canis infective larvae (13).…”
Section: Introductionmentioning
confidence: 99%